The influence of approximation in generalized uncertainty principle on black hole evaporation. Issue 4 (1st April 2022) - Du, Xin-Dong; Long, Chao-Yun
Abstract: The generalized uncertainty principle is often used to modify various thermodynamics systems by regarding the greater-than-equal relation as an approximate relation. We give a method to improve this approximation and compare the differences between the original and improved methods during the evaporation of black hole from two aspects of positive and negative parameters. Finally, we prove the rationality of the improved method and give some guiding opinions.